2010
DOI: 10.1007/s12079-010-0102-2
|View full text |Cite
|
Sign up to set email alerts
|

Mastering a mediator: blockade of CCN-2 shows early promise in human diabetic kidney disease

Abstract: In diabetes complications, CCN-2 (known originally as CTGF) has been implicated in diabetic nephropathy both as a marker and a mediator of disease. This commentary addresses CCN-2 in diabetic nephropathy, in the context of the recent publication of the first human study to inhibit CCN-2 bioactivity in diabetic kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…A phase 1 study of FG-3019 in patients with diabetic nephropathy showed good tolerability and a reduction in albuminuria (215, 216). In the Duchenne muscular dystrophy mouse model, FG-3019 was able to improve muscular strength and reduce impairment and fibrosis (217).…”
Section: Introductionmentioning
confidence: 99%
“…A phase 1 study of FG-3019 in patients with diabetic nephropathy showed good tolerability and a reduction in albuminuria (215, 216). In the Duchenne muscular dystrophy mouse model, FG-3019 was able to improve muscular strength and reduce impairment and fibrosis (217).…”
Section: Introductionmentioning
confidence: 99%
“…2) Aldosterone Receptor Blocker-Spironolactone [145] 3) Flavonoid compounds-astilbin [144] 4) FG-3019 Humanized monoclonal Ab that neutralizes the effect of CTGF in diabetic animal. [90] -it has shown to reduce albuminuria in diabetic nephropathy…”
Section: Navneet World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%
“…Synthesis of CTGF is stimulated by TGF-, hyperglycemia and AGEs, as well as CTGF itself. CTGF induces mesangial cell hypertrophy and cytoskeletal disassembling, upregulates cell production of fibronectin and collagens, and is also involved in epithelial-to-mesenchymal transition of tubular cells (Twigg, 2010;Connolly et al, 2003).…”
Section: Ctgfmentioning
confidence: 99%